Multi-User Searchable Encryption Scheme with User Revocation - Wu, Chia-Chi; Lin, Iuon-Chang; Liu, Ya-Hui (International Journal of Natural Sciences Research, 2016)
We improve the previous method to add the function of user revocation in searchable encryption scheme. When document owner doesn’t want to share someone he had shared, he can revoke the user who can’t retrieve the specific document. More importantly, the revocation process must not affect other authorized users, the scheme has to keep a low maintenance cost.